Neck metastasis in patients with T1-2 supraglottic cancer. Issue 3 (June 2018) - Tachibana, Tomoyasu; Orita, Yorihisa; Marunaka, Hidenori; Makihara, Sei-ichiro; Hirai, Misato; Gion, Yuka; Ikegami, Kana; Miki, Kentaro; Makino, Takuma; Noyama, Yasuyuki; Komatsubara, Yasutoshi; Kimura, Miyuki; et al.
Abstract: Objectives: Unlike glottic cancer, supraglottic cancer often presents with neck metastases. This different might be attributable to the location of the primary lesion. This study aimed to clarify the relationships between the sublocation of T1-2 supraglottic cancer, human papillomavirus (HPV) infection, neck metastasis, and prognosis of supraglottic cancer. Methods: This retrospective clinical study investigated 55 Japanese patients with T1-2 supraglottic cancer treated between 1994 and 2015. Results: Of 55 patients with T1-2 supraglottic cancer, neck metastasis was present at initial diagnosis in 14 patients (25.5%). Presence of neck metastasis was the only factor associated with worse prognosis of T1-2 supraglottic cancer (p = 0.004). In multivariate analysis, age <70 years (p = 0.033) and sublocation of the primary lesion in the superior epilaryngeal portion (p = 0.017) were significantly associated with presence of neck metastasis in multivariate analysis. Twelve (27.9%) of 43 patients showed positive results for human papillomavirus infection. However, human papillomavirus infection was not associated with prognosis, presence of neck metastasis, or primary lesion sublocation in T1-2 supraglottic cancer. Conclusion: Relatively young patients with supraglottic cancer at the superior epilaryngeal portion are more likely to show neck metastasis. Human papillomavirus infection was not associated with frequency of neck metastasis.